“Hungry for an Education”: Prevalence and Outcomes of Food Insecurity Among Students at a Primarily Undergraduate University in Rural Nova Scotia - Frank, Lesley (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2018)
This paper reports on food insecurity among students attending a university in rural Nova Scotia. In 2015, 1,030 students completed an online, 38-item cross-sectional survey. The results report that 38.1% of students experienced food insecurity during the previous 12 months. Food insecurity was statistically associated with living arrangements, source of funds for schooling, meal plans, and year of study. Poor overall health, poor mental health, high stress, and poor academic performance were significantly higher for food-insecure students. Students employed multiple coping strategies, with implications for academic success and long-term debt. Qualitative analysis revealed four themes related to insufficient money for food: inability to cover basic needs, health-related outcomes of persistent worry, loss of time from learning, and impacts on social life. This research demonstrates the need to re-evaluate funding policies for post-secondary education in Canada to ensure students can afford the costs of basic needs and educational costs.